2010
DOI: 10.1021/cm101694g
|View full text |Cite
|
Sign up to set email alerts
|

Growth of RuO2 Thin Films by Pulsed-Chemical Vapor Deposition Using RuO4 Precursor and 5% H2 Reduction Gas

Abstract: RuO 2 thin films were grown on thermal SiO 2 (100 nm) and Ta 2 O 5 (4 nm)/SiO 2 (100 nm) substrates at 230°C by pulsed-chemical vapor deposition using a RuO 4 precursor dissolved in blend of chosen organic solvent (with fluorinated solvents) and 95% N 2 /5% H 2 mixed gas as the Ru precursor and reactant gas, respectively. The phase of the deposited film, either being RuO 2 or Ru, was controlled by the N 2 /H 2 mixed gas feeding time. This was due to the fact that the time constant of the N 2 /H 2 mixed gas for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
85
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(89 citation statements)
references
References 29 publications
4
85
0
Order By: Relevance
“…8,9 The ATO (also TiO 2 ) films were grown at relatively low process temperatures (200−300°C). At these temperatures, the anatase phase, of which κ value and band gap are ∼40 and ∼3.4 eV, respectively, is thermodynamically stable.…”
Section: ■ Introductionmentioning
confidence: 99%
“…8,9 The ATO (also TiO 2 ) films were grown at relatively low process temperatures (200−300°C). At these temperatures, the anatase phase, of which κ value and band gap are ∼40 and ∼3.4 eV, respectively, is thermodynamically stable.…”
Section: ■ Introductionmentioning
confidence: 99%
“…11-13 A typical example can be found from the SrO and TiO 2 lm growth on the bottom electrode layers at a substrate temperature (T s ) of 370 C, 11,12 which becomes considerably less severe when the T s is decreased. 18,19 Therefore, understanding the chemical environment and resulting activity of the oxygen atoms in the underlying RuO x layer is crucially important for correctly understanding the ALD process of the TiO 2 lm on top, and for improving the resulting properties. 14,15 In the case of ALD of TiO 2 on the metal Ru electrode, using titanium tetraisopropoxide (Ti(O(C 3 H 7 )) 4 , TTIP) and O 3 as the Ti precursor and oxygen source, respectively, the O 3 in situ oxidized the Ru substrate, and the resulting $1 nm thick RuO 2 induced the phase transition of TiO 2 from anatase to rutile through the local epitaxial relationship.…”
Section: Introductionmentioning
confidence: 99%
“…However, effective SPEWE is primarily driven by the energetic barrier to the oxygen evolution reaction (OER) [12].Though many studies have found that RuO 2 is the most efficient catalyst for H 2 O splitting, it evolves fast toward an unstable form (RuO 4 ) and subsequently to its dissolution when the potential is over the thermoneutral potential (1.48 V at 25 C) [13,14]. It has been accepted that IrO 2 with slightly lower activity for OER obtains much higher durability than RuO 2 in strong acidic electrolyte [6,8,15,16].…”
Section: Introductionmentioning
confidence: 99%